How Facilitators use Affect to Help Workplace Employees Learn Creativity - Kirk D. Fleming (Adult Education Research Conference, 2010)
One way to foster workplace creativity is to position it as a learning process. How emotion influences this learning process, and how facilitators may or may not use it, is not fully understood.